Strategies of property developers and governments under carbon tax and subsidies - Yao, Qingzhen; Shao, Liangshan; Yin, Zimin; Wang, Junmei; Lan, Yue (Frontiers in Environmental Science, 2022)
Abstract: Implementing low-carbon houses is inseparable from the carbon tax and subsidy policies. Appropriate carbon taxes and subsidies can help to reduce household carbon emissions. This study aims to identify a suitable carbon tax and subsidy policy and investigate how this policy will affect the adoption of low-carbon housing. We classify programs including carbon taxes and subsidies into four categories: static carbon tax static subsidy, static carbon tax dynamic subsidy, dynamic carbon tax dynamic subsidy, and dynamic carbon tax static subsidy. Additionally, under various carbon tax and subsidy systems, the evolutionary stability strategies (ESS) of real estate developers and governments will be examined using evolutionary game theory. The case simulation results show that static carbon tax and dynamic subsidies are the best strategies. Government regulation is essential for the implementation of low-carbon housing. The higher the carbon tax and the property developer's profit, the higher the willingness of property developers to implement low-carbon houses and the higher the willingness of government regulation. Appropriate low-carbon subsidies will help property developers implement low-carbon houses. However, after reaching a certain point, low-carbon subsidies will make property developers less inclined to build low-carbon houses. The higher the cost of government regulation, the lower the probability of the low-carbon strategy of property developers, but the cost of government regulation has little impact on the government's regulation strategy.